Cartografia das normas de gênero: pincelando representações - Figueiredo, Bianca Araci de (2018)
Based on the biological differences observed in the bodies, Western society constructs definitions, normalizes relationships and assigns distinct social functions to women and men, in order to regulate behaviors and hierarchize relationships, composing a scenario of production and maintenance of inequalities due to gender. According to the bias of the everyday experiences of understanding each other as women and men, crossed by identifications and differences, this dissertation sought to map gender norms with high school students from two distinct school contexts, one from the periphery and another center, of schools located in the city of Sorocaba / SP. The research was constructed from the immersion in the school universe during a school year in each context. The constancy of the research led to the approximation of researcher-student relations, in order to transpose into a living description of the systems of cultural meanings of each school. Data were obtained from participant observation, especially in biology and physical education classes, in the three years of high school. In this process, the field diary proved to be an important instrument, being used to record what, as the researcher's view, weighed as the main daily events. A practical activity was carried out with eight focal groups, whose proposal consisted in the separation of images of culturally related items to women or men in three previously established categories: "What is for women?", "What is for men?" And " what is it of women and men? " Through this activity, we sought to identify the representations of gender norms stipulated and socially valued - or rejected - within each group and school. After the separation of the images, discussions were held, in which the students could position themselves as the result of the classification. Finally, there was the use of an individual structured questionnaire regarding family education, impressions of the school environment and personal pretensions with the end of high school and professional careers. Representations of women in both contexts presented similarities and differences, possibly as a result of accommodation and resistance. Girls from the periphery school avoid assigning activities, objects and instruments unique to women or men. They place a strong emphasis on the pluralities and multiplicities of gender identities, including understanding the network of social meanings and power relations involving women and men through gender norms. However, they seem to have difficulty visualizing women as intellectually equitable to men, attributing to them disciplines of accuracy and sports of strategy and logic, such as chess; while girls at the center school are somewhat conservative about gender norms, attributing aesthetic items such as hair dryers and creams, exclusive to 'women', so that rules seem to overlap with daily experiences that subvert them. These middle school girls are physically limited to the development of certain activities, but intellectually equitable in relation to men, categorizing items such as school subjects and chess as "women and men", thus not making distinctions in this regard. The boys from both schools presented more similarities than divergences in the response, which indicates the learning of a hegemonic gender norm, which crosses the various socio-cultural spaces. Finally, this study suggests that school is an important space for manifestation of reactions contrary to gender norms and that feminism has brought new perspectives and possibilities; however, cultural, economic and social factors can act as maintainers of traditional gender norms.